A novel porous Ti/TiN/Ti thin film as a working electrode for back-contact, monolithic and non-TCO dye-sensitized solar cells. Issue 4 (5th April 2017) - Shen, Po-Shen; Li, Ming-Hsien; Yang, Yu-Syuan; Sung-Yen Juang, Sean; Lin, Chia-Wei; Yin, Tan-Ya; Chen, Peter
Abstract : A porous electrode for use in back-contact, monolithic and non-TCO dye-sensitized solar cells was proposed. Abstract : In the present work, we develop a novel method to fabricate a porous titanium–titanium nitride–titanium (Ti–TiN–Ti) thin film for use as a conducting electrode in dye-sensitized solar cells (DSCs). Three non-conventional device architectures, namely back-contact (BC-DSCs), monolithic (m-DSCs) and TCO-glass free back-contact (non-TCO BC-DSCs) dye solar cells, using this porous electrode are constructed. The back-contact dye-sensitized solar cells and monolithic dye-sensitized solar cells deliver power conversion efficiencies of 4.53% and 3.16%, respectively. In these two devices, only one piece of TCO glass is required, which has the potential to reduce the cost and weight in comparison with the traditional sandwich device. Furthermore, we present a non-TCO back-contact DSC photovoltaic device. In this case, the fabrication cost of DSCs could be greatly reduced as FTO glasses are completely absent in the device. The non-TCO BC-DSCs yielded an overall conversion efficiency of 3.53%, which is 51% of that of standard conventional DSCs with the same thickness of photoactive TiO2 layer.